Does Traumatic Donor Cause of Death Influence Outcome after Lung Transplantation? A Single-Centre Analysis - Pilarczyk, Kevin; Heckmann, Jens; Carstens, Henning; Lubarski, Jura; Jakob, Heinz; Pizanis, Nikolaus; Kamler, Markus (The Thoracic and Cardiovascular Surgeon, 2017)
Background Owing to the shortage of donor organs in lung transplantation (LuTX), liberalization of donor selection criteria has been proposed. However, some studies suggested that donor traumatic brain damage might influence posttransplantation allograft function. This article aimed to investigate the association of donor cause of death (DCD) and outcome after LuTX.Methods A retrospective analysis of 186 consecutive double LuTXs at our institution from January 2000 to December 2008 was performed. DCD was categorized into traumatic brain injury (TBI) and nontraumatic brain injury (NTBI). In addition, NTBI was sub classified as spontaneous intracerebral bleeding (B), hypoxic brain damage (H), and intracerebral neoplasia (N).Results DCD was classified as TBI in 50 patients (26.9%) and NTBI in 136 patients (73.1%): B in 112 patients (60.2%), H in 21 patients (11.3%), and N in 3 patients (1.6%). Young male donors predominated in group TBI (mean age 36.0 ± 14.5 vs. 42.8 ± 10.7, p < 0.01; 29 males in the TBI group [58.0%] vs. 48 males in the NTBI group [35.3%], p < 0.01). Groups of DCD did not differ significantly by recipient age or gender, recipient diagnosis, donor ventilation time, or paO2/FiO2 before harvesting. TBI donors received significantly more blood (3.4 ± 3.8 vs. 1.8 ± 1.9, p = 0.03). A chest trauma was evident only in group T (n = 7 [3.7%] vs. 0 [0%], p < 0.001). Mode of donor death did not affect the following indices of graft function: length of postoperative ventilation, paO2/FiO2 ratio up to 48 hours, and lung function up to 36 months. One- and three-year survival was comparable with 84.4 and 70.4% for TBI donors versus 89.4% and 69.2% for NTBI donors. Five-year survival tended to be lower in the TBI group but did not reach statistical significance (43.4 vs. 53.9%).Conclusion This study indicates that traumatic DCD does not affect outcome after LuTX. These results can be achieved with an ideal donor management combined with an individual case-to-case evaluation by an experienced LuTX surgeon.
Keywords: transplantation; lung; airway; benign or congenital lesions